PENGARUH RETURN ON ASSETS DAN REPUTASI KANTOR AKUNTAN PUBLIK (KAP) TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN SEKTOR PERDAGANGAN, JASA DAN INVESTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Yulientinah, Dewi Selviani; Hidayat, Rahmat (LAND JOURNAL, 2025)
The going concern audit opinion is a consideration by the auditor if doubts about the ability of a company to maintain the survival of its business arise. This study aims to determine the effects of Return on Assets (ROA) and reputation of accounting firms on going concern audit opinions in companies in the trade, services and investment sectors listed on the Indonesia Stock Exchange (IDX). This study uses a quantitative approach. There are 47 companies that are sampled in the study. Data collection uses a purposive sampling method from companies in the trade, services and investment sectors listed on the Indonesia Stock Exchange in 2020-2023. The data analysis techniques used are the Hosmer and Lemeshow Goodness of Fit Test, Logistic Regression Analysis Test, Determination Coefficient Test, Partial Test (Wald Test) and Omnibus Tests of Model Coefficients. The results of the study partially show that ROA does not effect the going concern audit opinion, but the reputation of the public accounting firm effect the going concern audit opinion. The results of the study simultaneously show that ROA and the reputation of public accounting firms effect the audit opinion of going concern in companies in the trading, service and investment companies sector listed on the Indonesia Stock Exchange.